Flatness-based analysis and control design for 2 × 2 hyperbolic PDEs with nonlinear boundary dynamics. Issue 26 (2022) - Woittennek, F.; Irscheid, A.; Gehring, N.
Abstract: Distributed-parameter systems represented by linear one-dimensional 2 × 2 hyperbolic PDEs with nonlinear finite-dimensional differentially flat dynamics at one boundary and control acting linearly via the opposite boundary are considered. Flatness of the overall system, deduced from the flatness of the boundary system, allows for the parametrization of the systems solutions by the trajectory of a flat output. The state associated with this parametrization corresponds to the restriction of the flat-output trajectory to a compact interval. This state is intrinsically linked to a nonlinear hyperbolic controller form and associated with the original system variables by an invertible transformation. Moreover, it allows for immediate and constructive reachability analysis. State feedback for tracking a desired reference trajectory is achieved by choosing arbitrary stable closed-loop dynamics. A numerical example illustrates the control performance for different choices of the closed-loop dynamics.